Incorporation of Polybutadiene into Waterborne Polystyrene Nanoparticles via Miniemulsion Polymerization - Ronco, Ludmila Irene (2013)
The incorporation of polybutadiene in waterborne polystyrene nanoparticles by miniemulsion polymerization is expected to positively combine the properties of both materials,improving the impact resistance and toughness. The kinetics of the miniemulsion polymerization used to synthesize these hybrid nanomaterials and the effect of the reaction variables on the polymer microstructure and particle morphology were investigated. Both molecular microstructure and final particle morphology (core?shell, ??salami?? or threephase type) depended on the nature of the employed polybutadiene based rubbers and initiators. The mechanisms responsible for these effects were discussed.